2009
DOI: 10.1128/iai.00962-08
|View full text |Cite
|
Sign up to set email alerts
|

Cytolethal Distending Toxin Type I and Type IV Genes Are Framed with Lambdoid Prophage Genes in Extraintestinal Pathogenic Escherichia coli

Abstract: Five types of cytolethal distending toxin (CDT-I to CDT-V) have been identified in Escherichia coli.In the present study we cloned and sequenced the cdt-IV operon and flanking region from a porcine extraintestinal pathogenic E. coli (ExPEC) strain belonging to serogroup O75. We confirmed that similar to other CDTs, CDT-IV induced phosphorylation of host histone H2AX, a sensitive marker of DNA double-strand breaks, and blocked the HeLa cell cycle at the G 2 -M transition. The cdt-IV genes were framed by lambdoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 49 publications
2
56
0
1
Order By: Relevance
“…Five types of CDT (CDT-I to CDT-V) have been reported in pathogenic E. coli strains (Tóth et al, 2009a); among them CDT-V is the most recently identified (Janka et al, 2003), and the only type to be detected in Shiga toxin producing (STEC) and enterohaemorrhagic (EHEC) E. coli (Orth et al, 2006;Hinenoya et al, 2009;Hinenoya et al, 2014). Additionally, CDT-V has been detected in several strains of uncertain pathotype (Hinenoya et al, 2009;Tóth et al, 2009b), and in some of these strains it is the only identified toxin so far (Tóth et al, 2009b).…”
mentioning
confidence: 99%
“…Five types of CDT (CDT-I to CDT-V) have been reported in pathogenic E. coli strains (Tóth et al, 2009a); among them CDT-V is the most recently identified (Janka et al, 2003), and the only type to be detected in Shiga toxin producing (STEC) and enterohaemorrhagic (EHEC) E. coli (Orth et al, 2006;Hinenoya et al, 2009;Hinenoya et al, 2014). Additionally, CDT-V has been detected in several strains of uncertain pathotype (Hinenoya et al, 2009;Tóth et al, 2009b), and in some of these strains it is the only identified toxin so far (Tóth et al, 2009b).…”
mentioning
confidence: 99%
“…Accordingly the downstream region of the cdt locus as cdtC was always associated with a putative protease (rorf1) gene [12]. In contrast the upstream region of the cdt locus showed diversity and deletion was detected in some CDT-IV strains including APEC E250 strain.…”
Section: Exploration Of the Progressive Gene Loss In Upstream Region mentioning
confidence: 99%
“…The PCR primers used for (i) comparison the genomic organisations of the upstream regions of cdt loci between 28C [16] reference strain and APEC E250 [12]; (ii) the cloning steps of labelling, and (iii) screening for deletions after labelling are compiled in Table II. In vitro labelling the cdt-IV locus Introduction of a chloramphenicol resistance marker, mobilisation genes, an origin of replication, and an origin of transfer into cdt-IV locus of the avian pathogenic E. coli strain E250 was accomplished with the help of plasmid pSG704 [15] as it is depicted in Figure 1, pSG704 is a chloramphenicol-resistant derivative of the conjugative suicide vector pGP704 [15].…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
See 2 more Smart Citations